2021
DOI: 10.1007/s00402-021-04030-8
|View full text |Cite
|
Sign up to set email alerts
|

Similar biomechanical properties of four tripled tendon graft models for ACL reconstruction

Abstract: Purpose The present study tested and compared the biomechanical properties of four different triplicate graft tendon techniques. Methods 32 tripled tendons from the common extensor muscle of bovine fingers were tested on a material testing machine, passing the end loop over a metal rod of a clevis connected to the load cell on the upper side, and fixing the lower end to a clamp. The samples were divided into four groups: (A) tripled with a free end sutured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…Osteoarthritis is the most common disease of joints in the adult population [1][2][3][4]. In particular, the knee is the most frequent location for osteoarthritis, as its prevalence in adults is around 6%, rising as high as 40% among the 70-to-74-year-olds [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Osteoarthritis is the most common disease of joints in the adult population [1][2][3][4]. In particular, the knee is the most frequent location for osteoarthritis, as its prevalence in adults is around 6%, rising as high as 40% among the 70-to-74-year-olds [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…e biomechanical choice of the tendon graft, potentially based on predicted tendon sizes, should also be considered. However, a recent study assessed the biomechanical properties of four different methods of suture fixation to prepare triple tendon grafts and found similar properties between the groups [27].…”
Section: Discussionmentioning
confidence: 99%
“…The use of the soleus alone would have been insufficient due to the usual size of the wound defect, and also their combined use as bimuscular flap, helps to limit flexion and improve stability of a severely affected knee. 45,46 An option within the musculocutaneous local flap is the pedicled gracilis muscle flap, as it provides long, thin and versatile muscle coverage with a vascular pedicle and minimal donor site morbidity. Jung AJ et al 30 reported a case of soft tissue reconstruction using a reverse gracilis muscle flap, demonstrating its potency for knee area reconstruction or in addition to a medial or lateral gastrocnemius flap.…”
Section: Discussionmentioning
confidence: 99%